(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In this work, the technologies for obtaining and electrical characteristics of heterostructures based on SnO₂ films deposited on silicon (Si) substrates are investigated. SnO₂ films were obtained by thermal evaporation in vacuum, as a result of which structures of the Ni–SnO₂–n–Si–Ni type were created. Volt-ampere characteristics (I-V characteristics), photoluminescence and infrared absorption of samples of the p-SnO₂/n-Si heterostructure were studied. It was shown that the direct current in optimal heterostructures is 50–60 times higher than reverse, and conductivity is due to the tunnel-recombination mechanism. Photoluminescent studies have revealed the presence of nanocrystalline phases on the surface of silicon and features of recombination processes. The prospects of using the obtained heterostructures as solar converters and gas sensors are noted.